Health service user participation in interprofessional collaborative learning - a systematic review on the use of digital solutions / Die Teilnahme von Gesundheitsdienst-Nutzenden an interprofessionell kollaborativem Lernen - ein systematischer Review über den Gebrauch digitaler Lösungen - Kidritsch Anita; Lagiou Areti; Sakellariou Dikaios; Sakellari Evanthia (Sciendo, 2023)
Interprofessional collaborative learning is the interaction of health and/or social care professionals and/or students who are learning from service users' clinical data. Digital solutions in primary care facilitate interactive communication. This systematic review aims to identify which digital solutions can facilitate the participation of health service users in collaborative learning for interprofessional service providers, and how service users can participate with the use of digital solutions.